Potential Application of The Zero Waste Fashion Method to Optimize Fabric Usage - Faradillah Nursari; Fadhilaturrahmah Fadhilaturrahmah; Sari Yuningsih (Jurnal Ilmu Lingkungan, 2025)
The fashion industry is one of the largest economic sectors globally, having a significant impact on the environment and society. Comparison between zero waste fashion pattern techniques and conventional pattern techniques is the main focus in efforts to achieve sustainability in the fashion industry. The zero waste pattern cutting can reduce the amount of waste originating from the clothing industry which is formed during the clothing manufacturing process. This method can also be more environmentally friendly than conventional fashion patterns. There are two approaches to the design process from conventional patterns, namely construction patterns and draping patterns. Likewise, the zero waste fashion design process approach is 'from design to pattern' and from 'pattern to design'. All these approaches are compared to understand the design process, its potentioal, comparison, as well as its application and impact in the fashion industry. In this context, the zero waste fashion pattern is a technique for making clothing patterns which aims to produce clothing with less than 15% textile waste. This study applies qualitative techniques, namely literature studies and simulations which aim to understand and evaluate the differences between zero waste fashion patterns and conventional patterns in the fashion industry. The results of this research in achieving sustainability in the fashion industry, can be proven that the Zero-Waste pattern method has emerged as a more sustainable alternative. Being able to have a positive impact on the environment and the potential for more significant social development with increasing understanding of zero-waste fashion patterns, it is hoped that the fashion industry can experience a positive transformation towards more sustainable practices as a whole.